Análise do ensino de Física com base em Confronto de Opinião de Estudantes, Professores e Equipe Pedagógica - Rebello, Jacieli Fatima Lyra (2016)
This work evaluates some parameters of physics teaching at six public schools, four of them from Guarapuava – PR and another two from São Paulo – SP. The analysis was carried out using a Likert questionnaire. The questionnaire was composed of forty four sentences organized in three different groups, referring to the teacher, to the student and to school structure and the role of the pedagogical team. The questionnaire, when was applied to the three groups allowed a detailed analysis in not just only the factors involved in the teaching-learning process but also on the views of the groups regarding the competences of each group in the process of construction of knowledge. This analysis was made easier by the breaking up of the sentences in groups and also allowed a clear comparison between the opinions of each group regarding the different relevant aspects to the teaching-learning process. The sentences were elaborated on basis on the National Curricular Parameters, that control the quality of teaching, texts addressing conceptions regarding the educational theories and studies about ways to ease the adequation of the school reality with the theoretical assumptions on the objectives of the formation of high school students. This study and the evidences of trustworthiness of the answers were based on the opinions of nine hundred and thirteen students, eight teachers and ten pedagogues. A general analysis of each school was made and, due to the great number of applied questionnaires, sixteen of the forty four questions were elected to punctual analysis and opinion confrontation. By means of this analysis was possible to obtain interesting observations about the judgment of each group regarding the others, agreements and disagreements, besides the identification of signs of the traditional approach in physics classes and a correlation of this characteristic with the views of the students on the discipline. This identification gives us a starting point to methods that can improve the quality of teaching in each institution. The model of questionnaire employed can also be adapted to institutional evaluation or evaluation of other disciplines.